Implementasi Dan Analisis Perbandingan Algoritma ID3 Dan C4.5 Dalam Pengukuran Kepuasan Konsumen - Kaslani; Nurdiawan, Odi; Muhalim, Alvy (BULLET : Jurnal Multidisiplin Ilmu, 2024)
− Excellent service in order to achieve the goal, to achieve this it is necessary to improve services to these consumers, because these services are still not measured effectively and the services are still not using a method, to assess the services provided to consumers. The main purpose of the consumer satisfaction survey is to calculate customer satisfaction on CV. Bintang Terang Sejahtera by providing questionnaires that have been filled out by consumers, this is to improve and measure the extent of consumer satisfaction. The results of the accuracy of the ID3 algorithm obtained are 99.13% with details, namely Prediction Results Satisfied and Turns True Satisfied with 164 Data, Prediction Results Satisfied and turns True Dissatisfied with 2 Data, Prediction Results Dissatisfied and Turns True Satisfied with 0 Data, Prediction results are not satisfied and it turns out to be true, dissatisfied with 63 data. The results of the accuracy of the algorithm obtained are 95.63% with details, namely the Prediction Results Satisfied and it turns out True Satisfied with 160 Data, Prediction Results Satisfied and turns out to be True Dissatisfied with 6 Data, Predictions Results Dissatisfied and turns True Satisfied with 4 Data, Results Prediction is not satisfied and turns out to be true, dissatisfied with 59 data. comparison of the results of the algorithm, it can be seen from the table that the ID3 algorithm is 99.13% and the Decision Tree Algorithm is 95.63%, meaning that the ID algorithm is better than the decision tree algorithm.